The rebirth of home chemistry experiments: An international perspective and the Ukrainian context - Pavlo P. Nechypurenko; Oleksandra D. Kushnirova (Science Education Quarterly)
The use of home chemistry experiments has experienced a resurgence in recent years, particularly in light of the COVID-19 pandemic and the need for remote learning solutions. This perspective article examines the rebirth of home chemistry experiments from an international viewpoint, with a specific focus on the Ukrainian context. We differentiate between household and home chemistry experiments, discussing their advantages and challenges based on the work of Ukrainian educator Andrii Kyrylovych Hrabovyi and recent studies. The impact of home chemistry experiments on chemistry education is explored through international case studies from the United States, Finland, South Africa, and Brazil. We argue that even with the return to normal learning conditions in Ukrainian schools, home chemistry experiments should occupy a leading position among the means of teaching chemistry due to their ability to develop design and research skills, foster a caring attitude towards nature, and promote interest in studying chemistry. The experience of Luis Eduardo Doná in developing a home chemistry laboratory kit using affordable and accessible materials is highlighted as an example of how such initiatives can bridge the gap between theoretical learning and practical applications. We conclude that while home chemistry experiments remain a necessity in Ukraine, a review of their role in chemical education worldwide can be a significant step towards improving the quality of chemistry education.